A Community-Based Assessment of Hypertension and Some Other Cardiovascular Disease Risk Factors in Ngaoundéré, Cameroon - Olivier Pancha Mbouemboue; Diana Derew; Jacques Olivier Ngoufack Tsougmo; Marcel Tangyi Tamanji (International Journal of Hypertension)
Background and Objective. Cardiovascular diseases are primary causes of death worldwide with well documented risk factors whose varying impacts added to the complexity in CVD management dictate the need for region-specific studies. We aimed at investigating the interactions between CVD risk factors and hypertension in Ngaoundéré. Methods. A cross-sectional survey was carried out from March to August 2014. Sociodemographic, fasting blood glucose, blood pressure, and anthropometric data were recorded. Statistical analyses were carried out using SAS software version 9.1. Results. 700 adults resident in Ngaoundéré for at least two years consented and were included in the survey. Abdominal obesity, physical inactivity, and hypertension were the dominant risk factors recording 51.1%, 35.4%, and 20.4%, respectively. The prevalence of hyperglycaemia, tobacco consumption, obesity, and alcohol consumption was 5.6%, 8.3%, 9.6%, and 18.1%, respectively. Advanced age, hyperglycaemia, a divorced marital status, and alcohol consumption were independent determinants of high blood pressure. Conclusion. Physical inactivity, abdominal obesity, and hypertension were the most prevalent CVD risk factors, and the role of advanced age and hyperglycaemia in the occurrence of high blood pressure was reiterated. Health programs need to focus on effective screening, prevention, and control of CVDs in the Adamawa Region and Cameroon at large.